Deroua a new synthetic breed for the improvement of sheep production in Morocco - Benjelloun B.; Benbati M.; El Fadili M. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Composite breeds are known for their capacity to combine traits of interest for increasing productivity in sheep production. They could also meet the needs of the breeders who want to simplify and facilitate herd management and animal self-renewal. The Deroua sheep is a new composite breed obtained by a continuous crossbreeding plan including two main indigenous Moroccan breeds: the Dman a prolific breed with 50% of genes and Boujaad a rustic breed with 50% of genes. The present study described the performance of 395 ewes and 976 lambs of the new breed collected between 2011 and early 2018. Fixed factors that influence significantly those performances were defined using linear models. Estimated parameters for Deroua new breed ewe and lamb were comparable to other good breeds, e.g. 1.61 lambs and 20.5 kg respectively for the prolificacy and the litter size at weaning per lambing. The results showed that all traits and especially growth performance were significantly influenced by the studied fixed factors (ewe age, sex and birth mode). Performance could be increased by selection with appropriate criteria. The new breed should be reared under actual breeding conditions to record performance in the field. However, it was already concluded that the new breed would constitute a valuable resource for improving sheep productivity in Morocco under suitable breeding conditions.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)